2019
DOI: 10.1093/cercor/bhz007
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Associations Between Cortical Thickness and General Intelligence are Genetically Mediated

Abstract: The neural substrates of intelligence represent a fundamental but largely uncharted topic in human developmental neuroscience. Prior neuroimaging studies have identified modest but highly dynamic associations between intelligence and cortical thickness (CT) in childhood and adolescence. In a separate thread of research, quantitative genetic studies have repeatedly demonstrated that most measures of intelligence are highly heritable, as are many brain regions associated with intelligence. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 71 publications
(87 reference statements)
1
23
0
Order By: Relevance
“…Given the marked role of both depression and BMI on both sleep duration and global sleep quality, we selected these as phenotypes of interest for further analyses. As several cognitive factors were related to sleep duration and sleep quality, we selected general intelligence in this study, as this marker has been shown to be highly heritable and consistently relates to brain structure 42 . Next, we demonstrated that depression, IQ, and BMI have moderate phenotypic inter-correlations in unrelated HCP, eNKI, as well as full HCP samples ( Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the marked role of both depression and BMI on both sleep duration and global sleep quality, we selected these as phenotypes of interest for further analyses. As several cognitive factors were related to sleep duration and sleep quality, we selected general intelligence in this study, as this marker has been shown to be highly heritable and consistently relates to brain structure 42 . Next, we demonstrated that depression, IQ, and BMI have moderate phenotypic inter-correlations in unrelated HCP, eNKI, as well as full HCP samples ( Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, genetic factors influence cortical thickness in a systematic fashion where both functional and geometric constraints influence genetic correlation between and within brain systems 39,40 . Recent studies have indicated that phenotypic correlation between cortical thickness and intelligence, as well as BMI, is driven by additive genetic factors [41][42][43] suggesting a shared genetic basis of cortical thickness and non-brain traits. This raises the question whether the interrelation of sleep, mental, and physical health can be linked to the shared neurobiological mechanisms; and whether these relationships are driven by shared genetic factors.…”
mentioning
confidence: 99%
“…Furthermore, healthy adult subjects from the UK Biobank with higher polygenic risk scores for schizophrenia are more likely to have thinner cortices at the frontotemporal lobes ( Alnaes et al, 2019 ). Cortical thickness is associated with intelligence and mediated by genetics ( Schmitt et al, 2019 ), although these genetic associations are present starting at puberty and not in early childhood ( Brouwer et al, 2014b ). White matter surface area was larger in subjects with the rs13107325 SNP.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, variability in cortical thickness could be expected to show relatively straightforward and reliable associations with behavioural measurements (But also see (Natu et al, 2019)). The scientific literature indeed provides a lot of apparent evidence of associations between local thickness and psychometric variables, in particular with measures of the big domains of differential psychology, namely intelligence (Choi et al, 2008;Karama et al, 2009;Menary et al, 2013;Schmitt et al, 2019) and personality Owens et al, 2019;Riccelli et al, 2017a) . Additionally, the scientific literature suggests that local variability in CT could be further related to more specific psychological aspects such as anxiety trait (Kühn et al, 2011), impulsivity (Schilling et al, 2012), musical perception performance (Foster and Zatorre, 2010) or mentalizing abilities (Rice and Redcay, 2015) just to name a few.…”
Section: Introductionmentioning
confidence: 99%